2016
DOI: 10.18632/oncotarget.12507
|View full text |Cite
|
Sign up to set email alerts
|

IKK/NF-κB signaling contributes to glioblastoma stem cell maintenance

Abstract: Glioblastoma multiforme (GBM) carries a poor prognosis and continues to lack effective treatments. Glioblastoma stem cells (GSCs) drive tumor formation, invasion, and drug resistance and, as such, are the focus of studies to identify new therapies for disease control. Here, we identify the involvement of IKK and NF-κB signaling in the maintenance of GSCs. Inhibition of this pathway impairs self-renewal as analyzed in tumorsphere formation and GBM expansion as analyzed in brain slice culture. Interestingly, bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 87 publications
2
41
0
Order By: Relevance
“…Therefore, elimination of GSCs is considered to be a very effective approach for cure in GBM. A number of studies revealed that the inhibition of various signalling pathways reduced GSC survival and GSC properties . However, given that complete elimination of GSCs alone is difficult using inhibitors of these signal pathways, development of drugs with other strategies targeting GSCs is needed to improve patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, elimination of GSCs is considered to be a very effective approach for cure in GBM. A number of studies revealed that the inhibition of various signalling pathways reduced GSC survival and GSC properties . However, given that complete elimination of GSCs alone is difficult using inhibitors of these signal pathways, development of drugs with other strategies targeting GSCs is needed to improve patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed when the non-canonical NF-κB pathway was impaired through the attenuation of p52 or RelB [48]. A role for non-canonical NF-κB signalling in GSC self-renewal was also suggested by the independent observation that knockdown of RelB blocks the self-renewal activity of patient-derived glioma-initiating cells [49].…”
Section: Role Of Nf-κb In Glioblastoma Stem-like Cellsmentioning
confidence: 68%
“…Glioblastoma (GBM) is the most aggressive form of glioma, resistant to almost all available treatment modalities [1][2][3][4]. The molecular alterations in GBM are wellcharacterized and the involvement of many oncogenic pathways and molecules including NFкB-pathway are known [1,[5][6][7][8][9]. NFкB is an important signaling molecule, upregulating pro-inflammatory and hypoxic responses that contribute to tumor pathology and resistance to therapy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular alterations in GBM are wellcharacterized and the involvement of many oncogenic pathways and molecules including NFкB-pathway are known [1,[5][6][7][8][9]. NFкB is an important signaling molecule, upregulating pro-inflammatory and hypoxic responses that contribute to tumor pathology and resistance to therapy [8][9][10]. NFкB activation is known to promote tumor progression through mechanisms such as cell proliferation, apoptosis, angiogenesis, tumor metastasis, proinflammatory response, metabolic reprogramming etc.…”
Section: Introductionmentioning
confidence: 99%